Economic Recovery Through Community Empowerment to Reduce Impact of the Covid-19 - Sukiyani Sukiyani (Prosperity: Journal of Society and Empowerment, 2021)
The impact of the Covid-19 Pandemic Disaster is still very much felt by the economy of the people in the Special Region of Yogyakarta. The purpose of this research is to map the policies of the Provincial Government of the Special Region of Yogyakarta in empowering the community to the perpetrators of cooperative activities, micro, small and medium enterprises and to map the operational strategies carried out for the development of these policies. This study uses qualitative methods and uses secondary data from various kinds of literature such as books, articles, related journals regarding empowerment policies for actors in cooperative activities, micro, small and medium enterprises from the impact of the Covid-19 pandemic. The data analysis technique used in this research is descriptive analysis. The results of the research, it is known that the success of community empowerment policies for actors in cooperative activities, micro, small and medium enterprises in the Special Region of Yogyakarta from the impact of the Covid-19 pandemic disaster in the first quarter of 2021 experienced growth compared to the first quarter of 2020. The biggest contribution to economic growth in the Special Region of Yogyakarta in the first quarter of 2021 is the information and communication business field.